Iturin A Induces Resistance and Improves the Quality and Safety of Harvested Cherry Tomato - Mengxi Jiang (MDPI AG, 2021)
The soft rot disease caused by Rhizopus stolonifer is an important disease in cherry tomato fruit. In this study, the effect of iturin A on soft rot of cherry tomato and its influence on the storage quality of cherry tomato fruit were investigated. The results showed that 512 μg/mL of iturin A could effectively inhibit the incidence of soft rot of cherry tomato fruit. It was found that iturin A could induce the activity of resistance-related enzymes including phenylalanine ammonia lyase (PAL), polyphenol oxidase (PPO), peroxidase (POD), glucanase (GLU), and chitinase (CHI), and active oxygen-related enzymes including ascorbate peroxidases (APX), superoxide dismutases (SOD), catalases (CAT), and glutathione reductase (GR) of cherry tomato fruit. In addition, iturin A treatment could slow down the weight loss of cherry tomato and soften the fruit. These results indicated that iturin A could retard the decay and improve the quality of cherry tomato fruit by both the inhibition growth of R. stolonifera and the inducing the resistance.